Production of ficus elastica robusta leaf juice (daun tapak gajah) / Nor Aishah Ahmad Nor Azmi - Nor Azmi, Nor Aishah Ahmad (2008)
Ficus elastica robusta leaf juice was formulated with TSS 55°Brix and 60°Brix with pH 4.2. ficus elastica robusta, family Moraceae was obtained from botanical garden at Semenyih, Negeri Sembilan. Sensory analysis, mineral and crude fiber content, viscosity and colour measurement were carried out. The parameter was determined in order to know the acceptability of ficus elastica robusta leaf juice. From this study, the formulation with lower TSS (55°Brix) was most accepted by the panelists with mean score 6.5. From the analysis, formulation with 55°Brix contains 511.6 ppm of potassium and 33.02 ppm of calcium which was higher than formulation with 60°Brix. While, the percent of crude fiber in formulation 55°Brix was about 1.56% as compared to formulation 60°Brix was about 1.54% but there was no significantly difference between these two formulations. From this study, formulation with lower TSS (55°Brix) was recommended to produce the juice due to the higher mineral and crude fiber content compared to others.